ADAPTASI PUSAT JAJAN SEMI TERBUKA DI MASA PANDEMI MELALUI FASILITAS PENDUKUNG - Nediari, Amarena; Hendrassukma, Dila; Fanthi, Reno (Universitas Ciputra Surabaya, 2022)
The outbreak in 2020, has unconsciously impacted the trend of food court with semi-outdoor areas. Since open spaces are considered to have lower risk of spreading the virus compared to indoor areas. There are health protocols that must be obeyed to break the chain of virus transmission. Food court as a facility to provide culinary delights have survived during the outbreak as they have easy access supported with affordable prices. It is interesting that semi-outdoor food courts have opened since 2019 but become more popular in the pandemic era. It is found that food courts have supporting facilities to match the variety of activities in urban society other than food and beverages services. Semi-outdoor food court has an open space has natural lighting and the air is well circulated. The scope of this research is a semi-outdoor food court that has additional facilities in DKI Jakarta and its surroundings. Therefore, it has a potential to expand the area for further research. Why is the supporting facilities in food court are interesting to visit in this pandemic era? Each supporting facility has its own purposes in accommodating the community in urban society. The result of this research indicates that activities held in supporting facilities determine visitors and it is also expected to reduce the crowds. This research was carried out by descriptive research conducted in four semi-outdoor food court, selected by the different supporting facilities. It is hoped the result of this research will become recommendation in designing supporting facilities at semi-outdoor food courts to meet the health protocols during covid-19 pandemic. Keywords: Food court, outbreak, trend, semi-outdoor, urban society